Perancangan Coran Baja Cor SKD6 Menggunakan Simulasi Perangkat Lunak Pada Produk Side Core SD25R - Kusnowo, Roni; Ery Hidayat (Manutech : Jurnal Teknologi Manufaktur, 2021)
This study aims to produce a casting design for SD25R sidecore products with SKD6 material to be able to produce sound casting products or castings products that are free from defects with a scale of 1: 1. The sidecore SD25R is a casting product made for molded components for car wheels. This component is an imported product and in Indonesia no one has succeeded in supplying the needs of this component. The methodology used is simulation method, which is a method used to predict the defects of a cast material by using the SOLIDcast 8.2.5. Starting with the calculation of the channel system and the addition and design simulation using software as a tool in modeling the process metal casting before the actual metal casting process is carried out to reduce the risk of failure. In addition, this simulation can predict freezing temperature, cooling speed, the hottest area, and the porosity that occurs will be seen from this simulation, so it will reduce the trial and error process in the field. Based on the calculation of the gating system, the dimensions of the runner are 11x22x33 mm, the gates is 12x48 mm, the diameters of downsprue is 33 mm, and uses 2 top risers with a diameter of 150 mm, with a casting yield of 59.5%.  The simulation results with this software showed that the gating system design from the above calculations and the use of the top riser is more effective to produce a better product or sound casting product.